ВПЛИВ СТАБІЛІЗАТОРІВ НА РІСТ, ЖИТТЄЗДАТНІСТЬ І ФУНКЦІОНАЛЬНУ АКТИВНІСТЬ BRADYRHIZOBIUM JAPONICUM - Козар , С.Ф.; Скорик , В.В.; Усманова , Т.О.; Євтушенко , Т.А. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2012)
The research of stabilizators influence on the growth, viability, nodulation activity and efficiency of Bradyrhizobium japonicum was conducted. It was found, that sodium alginate in a concentration of 0,2 % has a positive influence on a growth and functional activity of rhizobia. It was established in field experiments with soybean of Poltava cultivar that presowing seed bacterization with Bradyrhizobium japonicum, that were cultivated with given stabilizator, the area of assimilatory surface of leaves, number of nodules, their mass and nitrogen-fixing activity as well as plants productivity, were increasing.